Serovar prevalence of Leptospira in semirural India and the development of an IgM-based indirect ELISA - Sara Chandy; Lokeshwaran Kirubanandhan; Priya Hemavathy; Anees Mohammad Khadeeja; Siby Jacob Kurian; Krishnan Venkataraman; Kristine Mørch; Dilip Mathai; Anand Manoharan (Journal of Infection in Developing Countries)
Introduction: Leptospirosis is a major public health problem in India. However, it has been underreported and under-diagnosed due to a lack of awareness of the disease, a functional surveillance system, and appropriate laboratory diagnostic facilities. Methodology: This multicenter study aimed to understand the Leptospira serovars causing leptospirosis in seven secondary-level hospitals in six states in India. Since early and accurate diagnosis of leptospirosis is one of the challenges faced by clinicians in India due to the poor specificity and sensitivity of commercially available diagnostic systems, an in-house indirect enzyme-linked immunosorbent assay (ELISA) was developed. Genomic DNA from L. interrogans serovar Canicola was used for polymerase chain reaction amplification, cloning, and expression of the lipL32 gene in E. coli to amplify, clone, and express the lipL32 gene. Results: Australis was the common serovar seen at all the study centers. Serovar Icterohaemorrhagiae was seen in samples from Tamil Nadu and Assam. In-house ELISA was standardized using the purified recombinant LipL32 polypeptide and was used to evaluate serum. Subsequently, acute serum samples from leptospirosis patients (n = 60) were screened. Compared to the gold standard, the microscopic agglutination test, sensitivity and specificity of the in-house ELISA was 95% and 90%, respectively. Conclusions: Understanding Leptospira serovars circulating in leptospirosis-endemic areas will help to formulate better vaccines. LipL32-based ELISA may serve as a valuable tool for early diagnosis of leptospirosis.